Postmodernism, economics and knowledge - Amariglio, Jack; Cullenberg, Stephen; Ruccio, David F. (Routledge, 2001)
Only in the past twenty years have debates surrounding modernism and postmodernism begun to have an impact on economics. This new way of thinking rejects claims that science and mathematics provide the only models for the structure of economic knowledge.